Influence of human milk oligosaccharides on adherence of bifidobacteria and clostridia to cell lines - Musilova, Sarka; Modrackova, Nikol; Doskocil, Ivo; Svejstil, Roman; Rada, Vojtech (Acta microbiologica et immunologica Hungarica, 2017)
Adhesion of gut bacteria to the intestinal epithelium is the first step in their colonization of the neonatal immature gut. Bacterial colonization of the infant gut is influenced by several factors, of which the most important are the mode of delivery and breast-feeding. Breast-fed infants ingest several grams of human milk oligosaccharides (HMOs) per day, which can become receptor decoys for intestinal bacteria. The most abundant intestinal bacteria in vaginally delivered infants are bifidobacteria, whereas infants born by cesarean section are colonized by clostridia. The influence of HMOs on the adhesion of five strains of intestinal bacteria (three bifidobacterial strains and two clostridial strains) to mucus-secreting and non-mucus-secreting human epithelial cells was investigated. Bifidobacterium bifidum 1 and Bifidobacterium longum displayed almost the same level of adhesion in the presence and absence of HMOs. By contrast, adhesion of Clostridium butyricum 1 and 2 decreased from 14.41% to 6.72% and from 41.54% to 30.91%, respectively, in the presence of HMOs. The results of this study indicate that HMOs affect bacterial adhesion and are an important factor influencing bacterial colonization of the gut. Adhesion of the tested bacteria correlates with their ability to autoaggregate.
Keywords: Gastrointestinal Microbiome; Oligosaccharides; Infant; feces; Humans; kojenec; střeva; Intestines; cell lines; mateřské mléko; střevní sliznice; Female; dospělí; autoaggregation; lidé; Bacterial Adhesion; Clostridium; buněčné linie; Feces; clostridia; Adult; bakteriální adheze; ženské pohlaví; Cell Line; Milk, Human; Male; bifidobacteria; oligosacharidy; human milk oligosaccharides; střevní mikroflóra; Bifidobacterium; mužské pohlaví; Intestinal Mucosa